2018
DOI: 10.1109/mvt.2018.2813422
|View full text |Cite
|
Sign up to set email alerts
|

Trusted 5G Vehicular Networks: Blockchains and Content-Centric Networking

Abstract: Institute of Electrical and Electronics Engineers Vehicular communications are already a reality, but they still need to evolve in order to support higher throughput and, above all, ultra-low latency to accommodate new use cases such as the fully autonomous car. In addition, cybersecurity must be guaranteed, since the risk of losing control of vehicles in the face of an attack is undoubtedly a matter of national security. This article presents the technological enablers so that all these requirements can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 12 publications
0
38
0
1
Order By: Relevance
“…The work [94] presented a blockchain-based broker mechanism for IoT devices in 5G networks, in which network resources can be securely leased to end users in a privacy-protected manner. Moreover, the study presented in [95] showed that the introduction of blockchain to network slicing can further improve the reliability of the content sharing in information-centric networks (ICN) [96].…”
Section: B Network Layermentioning
confidence: 99%
“…The work [94] presented a blockchain-based broker mechanism for IoT devices in 5G networks, in which network resources can be securely leased to end users in a privacy-protected manner. Moreover, the study presented in [95] showed that the introduction of blockchain to network slicing can further improve the reliability of the content sharing in information-centric networks (ICN) [96].…”
Section: B Network Layermentioning
confidence: 99%
“…It is noted that votes to validate a message are not required for n hop > 1. It is simply because the validation of message has been done by adjacent witness nodes (mining nodes at n hop = 1) through a camera or location/speed verification [48]. All other nodes beyond the first hop may not have access to validate the originator.…”
Section: A the Proposed Poqf Consensusmentioning
confidence: 99%
“…The convergence of blockchain in next-generation vehicular communications based on 5G opens up new opportunities to empower 5G V2X networks, capabilities, applications, and services, as given in Table 8. Some research works are based on the integration of blockchain with cellular networks in V2X communications [79] and [80]. The authors in [79] presented 5G-based vehicular networks that enable technologies, like Content Centric Networking (CCN) based on blockchain for secure vehicular communications.…”
Section: Integration Of Blockchain With Cellular Technology In V2xmentioning
confidence: 99%
“…Some research works are based on the integration of blockchain with cellular networks in V2X communications [79] and [80]. The authors in [79] presented 5G-based vehicular networks that enable technologies, like Content Centric Networking (CCN) based on blockchain for secure vehicular communications. The authors use CCN instead of TCP/IP and allowed blockchains to monitor the confidentiality of information quality, source, and authenticity of information shared among the participating vehicles.…”
Section: Integration Of Blockchain With Cellular Technology In V2xmentioning
confidence: 99%